Single‐Crystal Arrays: Self‐Aligned Single‐Crystalline Hexagonal Boron Nitride Arrays: Toward Higher Integrated Electronic Devices (Adv. Electron. Mater. 11/2015). (November 2015) - Tan, Lifang; Han, Jiangli; Mendes, Rafael G.; Rümmeli, Mark H.; Liu, Jinxin; Wu, Qiong; Leng, Xuanye; Zhang, Tao; Zeng, Mengqi; Fu, Lei
Abstract : A hexagonal‐boron nitride (h‐BN) self‐aligned single‐crystal array (SASCA) is reported by Lei Fu and co‐workers in article number 1500223. The h‐BN SASCA shows orderly alignment and uniformly distribution. Moreover, it exhibits highly accordant spatial orientation and homogenous domain size, which can realize highly integrated and individually switching field‐effect transistors (FETs) when serving as gate dielectrics. Additionally, circular h‐BN single‐crystals, which are considered as the building blocks of h‐BN SASCA, are also observed.